Exploring the transformation of chemical components and the discovery of anti-tumor active components in the fruit of Sinopodophyllum hexandrum - Tian, Xiang-mu; Wang, Shuai; Li, Tian-jiao; Yang, Xin-xin; Bao, Yong-rui; Meng, Xian-sheng (Frontiers in Nutrition, 2025)
IntroductionThe fruit of Sinopodophyllum hexandrum (FSH) is derived from Sinopodophyllum hexandrum (Royle) Ying, a plant belonging to the family Berberidaceae of the order Ranunculaceae. It is mainly distributed in the Himalayan alpine region, and born in the understory of forests, and wetlands at the edge of forests, thickets or grasses. FSH grows at an altitude of 2,200–4,300 meters above sea level. Its main pharmacological activities include anti-tumor, anti-inflammation, analgesia, heat clearing and detoxification. In the current experiment, ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was adopted for investigating the chemical components contained in FSH, their transformation patterns in vivo and the potential anti-tumor components, so as to provide an experimental basis for the utilization and development of the resources of FSH.MethodsThe chemical components of FSH and their transformation patterns in vivo were investigated by UPLC-Q-TOF-MS, and the potential anti-tumor active components were predicted from the in vivo transformed components of FSH by using a network pharmacology approach.ResultsTotally 85 chemical components were identified in FSH, among which, 61 were flavonoids and 24 were lignans. The above components were transformed in vivo, including 36 prototype components and 13 transformed products. As revealed by the results of network pharmacology on the prediction of anti-tumor components of FSH, 17 compounds such as Kaempferol, Uralenol, and 8-Prenylquercetin in FSH were used as the potential anti-tumor components.ConclusionIn this study, the chemical composition, in vivo transformed components of FSH and their metabolites are investigated, and the in vivo transformed components are predicted to have potential anti-tumor pharmacological activities. This study provides the experimental bases for the utilization and development of the resources of FSH.